Co-creation Method : The Role of Arts towards Impacting the Quality of Well-being - Mohamad Faizuan, Mat; Hasnul Jamal, Saidon; Rosalia, Saimon; Sarah Naemah, Aman Leong; Zuriawati, Ahmad Zahari; Nourah, Nasser Al-Nahari (Universidad Complutense de Madrid, 2023)
A preliminary review of past studies has shown that the method that was used to engage the community with arts is often articulated very poorly. In addition, formal evaluations and reflections on community art engagement projects are extremely rare. Therefore, this study aims to explore the co-creation method for community-engaged art with selected communities in Kampung Muhibbah, Kuching, Sarawak, Malaysia. The objective of the discussion is to highlight how co-creation can offer a participative approach for both art practitioners and non-art practitioners that contribute to elevating the quality of life. The research was done in a mixed method that utilized a co-creation project as a case study for data collection whereby interviews and participant observations were conducted in a qualitative method and a well-being evaluation score was done in a quantitative method. Results showed that the co-creation project could establish good interactions within the community through art activities and subsequently elevate their well-being quality. A deeper understanding of the co-creation method with community engagement can challenge the conventional participative art practice. The exploration of the co-creation method through art as a medium had indeed contributed extensively to the knowledge of co-creation practice in community engagement to elevate well-being.